Case of giant basal cell carcinoma around the base of the penis in an elderly patient. Issue 5 (15th March 2014) - Suyama, Takayuki; Teramoto, Yukiko; Yamamoto, Akifumi; Kuroda, Isao; Yoshikawa, Shusuke; Kiyohara, Yoshio
Abstract We report a case of an 85‐year‐old man with a doughnut‐shaped basal cell carcinoma around the base of the penis invading the cavernosum urethra. In cases in which curative resection is planned, the penis is resected, cystostomy is performed, and postoperative self‐management is required. In line with the patient's wishes and the fact that he was an elderly person living alone without family support, we decided to perform penis‐conserving surgery. Relapse occurred once, for which additional resection was conducted. Two years after the resection, there was no evidence of tumor recurrence. The therapeutic plan for elderly patients should be modified after considering the patient's social background, wishes, activity and life expectancy.